KAJIAN KENDALA KEBAHASAAN PELAKSANAAN STANDARISASI ADMINISTRASI DESA BAGI PAMONG DESA DI DAERAH ISTIMEWA YOGYAKARTA - Suhardi Suhardi (Jurnal Penelitian Humaniora, 2000)
Abstract The purposes of this study were (1) to describe linguistically constraint done by village administrator, (2) to describe extra-linguistic factor caused it, and (3) to identify linguistically error on the village administration books. The subjects of this study were (1) village administration and the stake holder of the book village administration, that was A, B, and C model, and (2) documentation of the village administration such as public administration, population and financial administration. The objects of this study were the opinion of village administration and error of linguistic. The sample of this study was determined by quota sampling so that these were 19 villages (5% from all villages in Yogyakarta Special Area). The sample of documentation was taken from those villages and there were 171 books of village administration involved A, B and C model. The determined sample of page book administration was done randomly. The instruments of the study were questioner and conservative guide. The method used to analyze data were distributional  and “padan” methods. The result of this study showed that the village administrator had linguistically constraint in applying of linguistically aspect of village administration. Village administrators very often had difficulties in choosing term (1.3%) combine sentences (9.2%) choosing words (10.5%) and often had difficulties in choosing terms (5.3%). Village administrator sometimes had difficulties in choosing words (30.3%), choosing terms (38.9%) and combining sentences (32.9%). Another linguistically constraints was that the village administrators did not know about some administrative technical terms, such as perihal, tentang, uraian, and  keterangan. These linguistically constraints were happen because of some factors, those were:mother tongues, using Javanese in conducting a meeting , propose, speak with another village administrator, and speak with guesses in the office, a government communication, and tacle of education village administration. Linguistically error found  in the village administration books were (1)using capital letter (15.7%). (2) cutting of the words (20.3%). (3) using words(20.3%). (4) using the numeral (26.3%). (5) using the borrowing words (18.7%), (6)using of intonation symbols (29.%), (7)formation of words (16%), (8)phrase structures (18.6%), (9) sentence structure (37,5%) and (10) choosing of words and terms (3.3%). In side of those, it can be found the speaking error in the implementation of book administration, as the lexical or grammatical interference from the Javanese to Indonesian Language. Keywords: Linguistically Constraint, standardization implementation of village administration